Specific primer design for microbiome profiling of the dengue vector Aedes aegypti based on 16S ribosomal DNA - Ariesaka, Kiky Martha; Sishartami, Lintang Widya; Weningtyas, Anditri; Nuryady, Moh Mirza; Wiratama, Arif Ladika; Bakhtiar, Fannia Yosa (Universitas Islam Negeri Sumatera Utara, 2025)
Identification of the microbiome in the dengue vector Aedes aegypti is crucial for developing effective vector control strategies. The 16S ribosomal DNA (rDNA) gene is frequently used as a genetic marker in microbiome analysis. This study aimed to design and validate specific primers to identify Serratia and Wolbachia in Aedes aegypti. The study employed Primer-BLAST using DNA sequence data from NCBI (accession numbers OR801069.1 for Serratia and MN046789.1 for Wolbachia). The designed primers included: for Serratia—Forward 5’-GTCGACTTTGATCCTGGCTCAG-3’ and Reverse 5’-TCAGCCTGTTTCCAATGACC-3’; and for Wolbachia—Forward 5’-TGATGAAGTTAGCTTGCTAACG-3’ and Reverse 5’-ACGGCTGAGTGAACGGGTG-3’. Validation was conducted through PCR, followed by visualization of the amplification products using 1.5% agarose gel electrophoresis. PCR amplification revealed distinct DNA bands of 766 bp for Serratia and 556 bp for Wolbachia, confirming primer specificity. The Sanger sequencing results were validated using BLAST, showing high alignment with reference strains in the GenBank database. The specific primers based on the 16S rDNA gene are effective for detecting Serratia and Wolbachia in Aedes aegypti.